Public private partnerships as long term policy’s tools: theoretical bases and analysis of the institutional framework for the colombian case (2014)
This article makes a check from Public Private Partnership (PPP) as a Long- Term Public Policy Instrument. This form of cooperation receive influences from processes of State Reform, and implementation of principles and elements from New Public Management and Governance or New Governance. In the colombian case, it is argued that after two years after its implementation and taking into account its long term carácter, it observes a low participation in the presentation of projects using this instrument, that although grants benefits to private sector, financing mechanisms, low motivation and institutional capability are factors that may influence in the results down this way of cooperation. The work is divided in three topics: a review of theory basis, institutional rules applied to the colombian case and conclusions.